Economic Consequences of Mispredicting Utility - Bruno S. Frey; Alois Stutzer (Institute for the Study of Labor (IZA), 2013)
In a simple conceptual framework, we organize a multitude of phenomena related to the (mis)prediction of utility. Consequences in terms of distorted choices and lower wellbeing emerge if people have to trade-off between alternatives that are characterized by attributes satisfying extrinsic desires and alternatives serving intrinsic needs. Thereby the neglect of asymmetries in adaptation is proposed as an important driver. The theoretical analysis is consistent with econometric evidence on commuting choice using data on subjective well-being. People show substantial adaptation to a higher labor income but not to commuting. This may account for the finding that people are not compensated for the burden of commuting.
Keywords: A12; D11; D12; D84; I31; J22; 330; adaptation; extrinsic/intrinsic attributes; individual decision-making; misprediction; subjective well-being; time allocation